Design and characterization of controlled release tablet of metoprolol - Gautam Singhvi; Ravi Ukawala; Harish Dhoot; Suresh Jain (Wolters Kluwer Medknow Publications, 2012)
Metoprolol succinate is a selective beta-adrenergic receptor blocker useful in treatment of hypertension, angina and heart failure. The purpose of the present work was to design and evaluate controlled release matrix type tablet of Metoprolo succinate using HPMC K15M and Eudragit (RLPO and RSPO) as a matrix forming agents. Effect of various polymer alone and combinations were studied in pH 1.2 buffer using USP type II paddle at 50 rpm. HPMC was used to form firm gel with Eudragit polymer. Formulation with Equal proportion (1:1) of Eudragit RSPO and RLPO showed optimum drug release t50 =7 hrs and t100 =16 hrs indicate optimum permeability for drug release from matrix. The drug release mechanism was predominantly found to be Non-Fickian diffusion controlled.